Melanin pigments from sediment-associated Nocardiopsis sp. marine actinobacterium and antibacterial potential - R Sundar; Pitchiah Sivaperumal (Wolters Kluwer Medknow Publications, 2022)
To extract the melanin pigment from marine microbes and their biological potential, the present study was done. Isolation and identification of the melanin-producing Nocardiopsis sp. were obtained from the sediment samples. Zone of inhibition and minimal inhibitory concentration test was performed using melanin. Melanin was extracted from sediment-associated marine Nocardiopsis sp. In the present study, marine actinobacterium was identified by the conventional method, and the isolate was identified as Nocardiopsis sp. Melanin was extracted, and antibacterial activities were performed against different pathogens and the highest zone of inhibition is more in the E. coli while related to another two species. From previous observation done by Fu et al., they have said that marine actinobacteria have the ability of antimicrobial activity, which is very much helpful in producing the potential antimicrobial drugs this was similar to our study that marine actinobacteria have the capability to produce melanin pigment, and at the same time, it helps as to show the antibacterial activity. We concluded that melanin is produced by the Nocardiopsis sp. We also found that melanin extracted from the Nocardiopsis sp. of marine actinobacterium also has an antibacterial effect.